2016
DOI: 10.5114/ceji.2016.60991
|View full text |Cite
|
Sign up to set email alerts
|

Association of the polymorphisms of TRAF1 (rs10818488) and TNFAIP3 (rs2230926) with rheumatoid arthritis and systemic lupus erythematosus and their relationship to disease activity among Egyptian patients

Abstract: Aim of the studyRecent studies demonstrated the association of tumor necrosis factor α-induced protein 3 (TNFAIP3) (rs2230926) and tumor necrosis factor receptor associated factor 1 (TRAF1) (rs10818488) with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) in different populations. We aimed at determining whether they confer susceptibility to SLE and RA in Egyptian population and if there is any relation to disease activity and auto-antibodies profile.Material and methodsA case-control study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
13
0
1
Order By: Relevance
“…SLE or SSc patients with an intron SNP (Figure 2 C) predisposes for increased risk for either renal involvement ( 132 ) or aggravated disease with fibrosing alveolitis and pulmonary hypertension ( 133 ). Similarly, RA patients with a previously described functional SNP (Figure 2 E) had more swollen joints and increased disease activity scores (DAS28) compared to RA patients without this SNP, indicating worse clinical prognosis ( 9 , 117 ). Finally, AIH patients with an upstream SNP (Figure 2 A) harbored increased liver enzymes and more cirrhosis at disease presentation compared to patients without this SNP ( 109 ).…”
Section: A20/tnfaip3 In Autoinflammatory and Autoimmune Patientsmentioning
confidence: 63%
See 1 more Smart Citation
“…SLE or SSc patients with an intron SNP (Figure 2 C) predisposes for increased risk for either renal involvement ( 132 ) or aggravated disease with fibrosing alveolitis and pulmonary hypertension ( 133 ). Similarly, RA patients with a previously described functional SNP (Figure 2 E) had more swollen joints and increased disease activity scores (DAS28) compared to RA patients without this SNP, indicating worse clinical prognosis ( 9 , 117 ). Finally, AIH patients with an upstream SNP (Figure 2 A) harbored increased liver enzymes and more cirrhosis at disease presentation compared to patients without this SNP ( 109 ).…”
Section: A20/tnfaip3 In Autoinflammatory and Autoimmune Patientsmentioning
confidence: 63%
“…NF-κB activation is tightly controlled by several mechanisms, including the key regulatory (de)ubiquitinating enzyme A20 or tumor necrosis factor α-induced protein 3 (TNFAIP3) ( 6 ). Genetic studies have demonstrated the association of TNFAIP3 single nucleotide polymorphisms (SNPs) with multiple human diseases ( 7 ), such as systemic lupus erythematosus (SLE) ( 8 10 ), rheumatoid arthritis (RA) ( 9 ), and Crohn’s disease (CD) ( 11 , 12 ). A20/TNFAIP3 regulates crucial stages in immune cell homeostasis, such as NF-κB activation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…TNF‐receptor associated factor (TRAF) proteins are key adaptor molecules that play critical roles in immune cell signaling [22,23]. The TRAF1 gene encodes tumor necrosis factor (TNF) receptor associated factor 1, which is thought to be associated with a variety of TNF receptor family members [24]. By the construction of TRAF1‐pmir‐GLO and using dual‐luciferase reporter assay system, we initially confirmed that the target of miR‐483 is TRAF1.…”
Section: Discussionmentioning
confidence: 84%
“…Based on the consideration of genetic heterogeneity among different ethnic populations and possible false positive results, multiple studies have been subsequently performed to test whether the TRAF1 / C5 rs10818488 and rs3761847 polymorphisms are associated with RA in different ethnic populations [21-39]. Nevertheless, the results were inconsistent, and this discrepancy might be due to different sample sizes, genetic backgrounds, clinical heterogeneity and publication bias, etc.…”
Section: Introductionmentioning
confidence: 99%